2018
DOI: 10.1039/c8ra05021j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin modified niosomes to encapsulate hydrophilic compounds

Abstract: Incorporation of β-cyclodextrin into niosomes considerably increased the encapsulated amount and the delivery rate of a hydrophilic molecular probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…The average diameter remained similar (96.1 AE 0.9 nm) with homogeneous size distribution (0.434 AE 0.007 nm) aer encapsulation of the niosomes in the hydrogel and subsequent release. These ndings were also corroborated by FE-SEM, which showed the presence of spherical niosomes 46 within the k-C : gelatin polymer matrix with a size distribution in agreement with DLS data (Fig. 4).…”
Section: Stability Of Rsv-niosomes Aer Encapsulation and Hydrogel Desupporting
confidence: 81%
See 1 more Smart Citation
“…The average diameter remained similar (96.1 AE 0.9 nm) with homogeneous size distribution (0.434 AE 0.007 nm) aer encapsulation of the niosomes in the hydrogel and subsequent release. These ndings were also corroborated by FE-SEM, which showed the presence of spherical niosomes 46 within the k-C : gelatin polymer matrix with a size distribution in agreement with DLS data (Fig. 4).…”
Section: Stability Of Rsv-niosomes Aer Encapsulation and Hydrogel Desupporting
confidence: 81%
“…1). 46 The so obtained niosomes were subsequently mixed with a suitable amount of a mixture of k-C and gelatin (1 : 1 mass ratio, 4% w/v) in water and gently heated. The hydrogel was obtained aer cooling the mixture down to room temperature (RT) (ESI, Fig.…”
Section: Synthesis and Characterization Of Hydrogels Containing Rsv-nmentioning
confidence: 99%
“…Span 40 and CHE were selected because of their higher hydrophilicity with respect to Span 60 and CH, with the aim to improve the entrapment of a hydrophilic component such as ADM_09. HPβCD was selected with the same purpose, since recent studies reported a possible interaction between cyclodextrins and R-α-lipoic acid [35,36] and a positive effect of the cyclodextrins on hydrophilic drug entrapment in niosomes [37]. As shown in Table 2, modifying the lipidic phase ratio (batches 1, 2, and 3), the particle size and PDI worsen, showing that the components ratio in the formulation cannot be varied without changing the niosomes' characteristics.…”
Section: Preparationmentioning
confidence: 99%
“…The hydrophilic components that were introduced in order to increase the drug entrapment, Span 40 and CHE, unexpectedly reduced the drug entrapment. In addition, the attempt to improve drug entrapment using a cyclodextrin (HPβCD) did not produce the desired effect, even if in the literature a positive effect of cyclodextrins on hydrophilic drug entrapment in niosomes was reported by Machado et al 2018 [37].On the other hand, Machado et al observed a better effect of βCD on the entrapment of a hydrophilic dye in niosomes with respect to its derivative modified amphiphilic HPβCD; however, for our application, it is not possible to change the HPβCD (FDA-approved for a parenteral use) with a more lipophilic compound, such as the natural βCD, because of its parenteral toxicity. The selected composition was then Span 60, 8 mg/mL; CH, 5.73 mg/mL; SOL, 5.33 mg/mL; NPG, 1.58 mg/mL; and ADM_09, 1.4 mg/mL.…”
Section: Preparationmentioning
confidence: 99%
“…The TEM image in Figure 4b showed that quercetin-niosomes were spherical or oval in shape. The entrapment efficiency of quercetin-niosomes was 87.3 ± 1.6%, which was higher than those in the range of 48.4% to 78.4% in previous works [37,43,44]. The increased drug entrapment efficiency may be attributed to the affinity between drugs and the bilayers of niosomes [45].…”
Section: Resultsmentioning
confidence: 61%